2007
DOI: 10.1111/j.1471-8286.2007.01760.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of 150 novel microsatellite markers for Zhikong scallop (Chlamys farreri)

Abstract: We isolated and characterized 150 novel microsatellite markers of Zhikong scallop ( Chlamys farreri ) from three simple sequence repeat-enriched libraries constructed with (GA) 15 and (CA) 15 . The polymorphism was assessed with 48 individuals, and the result showed the number of allele ranged from two to 30, with an average of 8.4 alleles/locus. The values of observed and expected heterozygosities ranged from 0.0791 to 0.9878 and from 0 to 1.0000, respectively. Sixty-five loci showed significant departure fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 2 publications
2
38
0
Order By: Relevance
“…The mean overall observed heterozygosity found in this study, 0.286 for A. opercularis and 0.275 for M. varia , is within the range described in scallops after the analysis of allozyme loci, 0.016 for Lyropecten nodosa (Coronado et al 1991) and 0.321 for Chlamys distorta (Beaumont and Beveridge 1984), but lower than the values inferred from the high polymorphic microsatellite loci which usually exceed 0.80 (Gjetvaj et al 1997; Kenchington et al 2006; Zhan et al 2007). The level of genetic diversity reported here for the two scallops was similar, contrasting with the data provided by allozyme loci (Beaumont and Beveridge 1984) and mtDNA (Fernández‐Moreno et al 2008) that revealed higher levels in M. varia than in A. opercularis .…”
Section: Discussionsupporting
confidence: 76%
“…The mean overall observed heterozygosity found in this study, 0.286 for A. opercularis and 0.275 for M. varia , is within the range described in scallops after the analysis of allozyme loci, 0.016 for Lyropecten nodosa (Coronado et al 1991) and 0.321 for Chlamys distorta (Beaumont and Beveridge 1984), but lower than the values inferred from the high polymorphic microsatellite loci which usually exceed 0.80 (Gjetvaj et al 1997; Kenchington et al 2006; Zhan et al 2007). The level of genetic diversity reported here for the two scallops was similar, contrasting with the data provided by allozyme loci (Beaumont and Beveridge 1984) and mtDNA (Fernández‐Moreno et al 2008) that revealed higher levels in M. varia than in A. opercularis .…”
Section: Discussionsupporting
confidence: 76%
“…The number of polymorphic microsatellite loci obtained with respect to the total sequences examined in A. opercularis (6.0%) is higher than that yielded by enriched libraries constructed in the scallop Mizuhopecten yessoensis (4.6%, An et al 2005), the oyster Crassostrea virginica (2.4%, Reece et al 2004) or the pearl oyster Pinctada maxima (0.2%, Evans et al 2006), and lower than that obtained in other scallops, Chlamys farreri (12.5%, Zhan et al 2007), Pecten maximus (15.8%, Watts et al 2005) and C. nobilis (27.5%, Ma and Yu 2009) or the oyster C. gigas (19.6%, Li et al 2003). The efficiency of the isolation of microsatellites as usable markers might be affected by both biological and technical factors.…”
Section: Discussionmentioning
confidence: 61%
“…In this study, we used Zhikong scallop (Chlamys farreri) as a target species to compare the efficiency of five popular methods derived from the above three strategies. Microsatellite markers in Zhikong scallop show several unique characteristics such as wide spread of null alleles (Zhan et al, 2007a(Zhan et al, , 2007b and poor transferability among scallop species (Zhan et al, 2005). If the strategies work efficiently in Zhikong scallop, they are also expected to be robust candidates for other species.…”
Section: Introductionmentioning
confidence: 98%